Nutritional Status and Dietary Pattern of Under-five Children in Urban Slum Area - Vinod, Narkhede; Swarnakanta, Likhar; Pitale , Smita; Durge , Pushpa (National Journal of Community Medicine, 2011)
Nutrition of pre-school children (0-5 years age group) is of paramount importance because the foundation for lifetime health, strength and intellectual vitality is laid during this period. The study was aimed to assess the nutritional status and dietary pattern of children below five years of age. It was a community based cross-sectional study in children below five years of age from Urban slum, Nagpur. A house-to-house survey was done. By systematic random sampling 434 children below five years of age were included in the study. Every child was subjected to anthropometric measurements using standard technique. Dietary survey was done in 20% subsample. 52.23 % were suffering from various grades of malnutrition. 32.18 % children were in grade I, 16.09 % in grade II, 3.46 % in grade III and 0.5 % in grade IV malnutrition. The mean calorie intake of children in the age group 2-3 years was 842.6 Kcal, 3-4 years was 956.12 Kcal and 4-5 years was 1096.24 Kcal respectively. Nutritional rehabilitation centers should be started in the community and linked with health centers to treat less severely affected undernourished children.